Large area silicon drift detectors system for high precision timed x-ray spectroscopy. (1st September 2022) - Miliucci, M; Iliescu, M; Sgaramella, F; Bazzi, M; Bosnar, D; Bragadireanu, M; Carminati, M; Cargnelli, M; Clozza, A; Curceanu, C; Deda, G; De Paolis, L; et al.
Abstract: The current work presents the optimization of large area silicon drift detectors developed by the SIDDHARTA-2 collaboration for high precision x-ray measurements of light exotic atom transitions. Two different radiation sources were employed in the study: an x-ray tube, for investigating the energy resolution and the charge collection efficiency of the device in the range 4000 eV–13 000 eV, and a β − 90 Sr radioactive source for measuring the timing response, thus qualifying the charge drift parameters inside the semiconductor. The study reports the spectroscopic response optimization, together with the tuning of the electron dynamics for the given Silicon technology, by adjusting the applied electric field and the working temperature, which allow a good control of the device's performances for high precision, timed x-ray spectroscopy applications.